Emission Enhancement and Intermittency in Polycrystalline Organolead Halide Perovskite Films - Cheng Li (Molecules, 2016)
Inorganic-organic halide organometal perovskites have demonstrated very promising performance for opto-electronic applications, such as solar cells, light-emitting diodes, lasers, single-photon sources, etc. However, the little knowledge on the underlying photophysics, especially on a microscopic scale, hampers the further improvement of devices based on this material. In this communication, correlated conventional photoluminescence (PL) characterization and wide-field PL imaging as a function of time are employed to investigate the spatially- and temporally-resolved PL in CH3NH3PbI3−xClx perovskite films. Along with a continuous increase of the PL intensity during light soaking, we also observe PL blinking or PL intermittency behavior in individual grains of these films. Combined with significant suppression of PL blinking in perovskite films coated with a phenyl-C61-butyric acid methyl ester (PCBM) layer, it suggests that this PL intermittency is attributed to Auger recombination induced by photoionized defects/traps or mobile ions within grains. These defects/traps are detrimental for light conversion and can be effectively passivated by the PCBM layer. This finding paves the way to provide a guideline on the further improvement of perovskite opto-electronic devices.